Zmiany w podatku VAT w kontekście przeciwdziałania zjawisku unikania i uchylania się od opodatkowania w latach 2016–2018 - Robert Wolański (Studia i Materiały)
The article discusses the problem of legal changes in VAT introduced in 2016–2018, which counteracting the avoidance and evasion of this tax. The purpose of this article is to determine causes, methods and effects of introducing these changes. To realize the purpose of article, as a research method, used the overview of selected literature, legal acts and statistical data on tax evasion and avoidance. As the result of the article is the verification of following thesis: the legitimacy of choosing VAT to reduce the tax gap, simultaneously increasing budget revenues; changes in VAT lead to a reduction of avoidance and evasion, at the same time greatly complicate the application and settlement of this tax; negative effects of introduced changes for the smallest enterprises (especially micro and small).